Estudo da influência da pressão no escoamento bifásico gás-líquido em golfadas em dutos horizontais - Pandolfo, Diego (2011)
Two-phase flows are present in many industrial applications, such as the oil industry, chemical, and nuclear power plants because they are intrinsic to the transport process involving mixtures in pipes, such as gas-liquid, and thus the target of intense study. By variation of factors such as speed of the phases, dimensions and orientation of the pipe, occur certain geometric configurations known as flow patterns. Often such flows occur in pressurized systems, due to extreme operating conditions with pressure drop. Within this context, the objective of this study is to characterize experimentally the flow pattern in horizontal full developed in pressurized pipelines. A fully instrumented bench, which is on the premises of LACIT (Laboratory for Thermal Science), was adapted to measure the parameters of normal flow at high pressure. Was performed to verify the calibration of the sensors and meters installed in the experimental circuit. For monitoring of flow, surface speeds and pressures, we used the computer program for data acquisition and monitoring in LabView programming language developed in LACIT. In order to verify the influence of pressure on the slug flow pattern, experimental tests were performed with flow pressures at the output of controlled waste ranging from 1 to 5 bar pressure. From the images acquired with the use of a camera's high rate of image acquisition, processing was performed using an image recognition program developed in Matlab platform. After processing and data analysis were checked characteristic parameters of the flow in intermittent flow, for example, elongated bubble length, length of the slug, void fraction, frequency of passage of unit cells and intermittency factor.